Improvement In Oxygen Delignification Of Oil Palm Empty Fruit Bunches (Efb) Soda-Aq Pulp And Use Of Experimental Design For Process Optimisation - Ng, Soo Huey (2011)
The delignification of oil palm (Elaeis guineensis) empty fruit bunch fibres soda-AQ pulp by oxygen is limited to 38%, to avoid substantial cellulose degradation. To enhance the effectiveness of oxygen delignification (O stage), small amounts of hydrogen peroxide (H2O2) with and without anthraquinone (AQ) are added during oxygen delignification, which are known as the hydrogen peroxide reinforced oxygen delignification (OP stage) and AQ-aided OP stage respectively. The preliminary study of the addition of hydrogen peroxide and anthraquinone (AQ) to oxygen delignification has shown their potential on improving kappa number (Kn) reduction and pulp brightness. Hence, the interaction effects of hydrogen peroxide and anthraquinone, and the other three process variables viz. reaction temperature (T), reaction time (t) and alkaline charge (Ac) on oxygen delignification of pulp produced from oil palm (Elaeis guineensis) empty fruit bunch fibre are statistically investigated by employing a half two-level factorial (2k-1) experimental design in order to screen out the insignificant effects. Based on the factorial models built, H2O2 (P), reaction temperature (T) and alkali charge (Ac) are significant to all of the responses. Besides, the impairment to the pulp viscosity by a relatively higher level of H2O2 (2.0% on the oven-dry weight of pulp) is found to be significantly countered by adding a small amount of anthraquinone. Furthermore, all factorial models built are also statistically and experimentally validated. The optimisation of the AQ-aided OP stage is operated with response surface methodology (RSM) through central composite design (CCD) with three independent variables namely H2O2* (P, 0.25-2.00%), reaction temperature* (T*, 70-110 °C), and alkali charge* (Ac*, 1.2-2.8%) and the fixed variables are 30 min reaction time and 0.02 % AQ.